Az ISO 9000 szabványok változásai - Marosi, Tibor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The International Organization for Standardization issued the new ISO 9001:2008 standard with title Quality Management systems. Requirements at 15 Nov 2008. In spite of arrangements lasting more years the requirements of the standard basically have not changed. The main goal of changes was in one hand the more understandable and clearer text, on the other the increasing compatibility with the standard ISO 14001. This paper gives an explanation of changes in requirements ISO 9001:2008. These changes have been taken into consideration by the users if they want to suit the expectations of the new document.